The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1038/bmt.2015.280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immune modulation in relapsed peripheral T-cell lymphomas after post-allogeneic stem cell transplantation: a study by the Société Française de Greffe de Moelle et de Thérapie Cellulaire (SFGM-TC)

Abstract: Peripheral T-cell lymphoma carries a poor prognosis. To document a possible graft-versus-lymphoma effect in this setting, we evaluated the impact of immunomodulation in 63 patients with peripheral T-cell lymphoma who relapsed after allogeneic transplant in 27 SFGM-TC centers. Relapse occurred after a median of 2.8 months. Patients were then treated with nonimmunologic strategies (chemotherapy, radiotherapy) and/or immune modulation (donor lymphocyte infusions (DLI) and/or discontinuation of immunosuppressive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(41 reference statements)
0
2
1
Order By: Relevance
“…Limited data suggest the utility of DLI in relapsed lymphoma patients after allo-HCT [6,[15][16][17][18][19][20]. More recently, French investigators showed excellent response rates with DLI in peripheral T cell lymphoma patients who relapsed after allo-HCT [21]. In our study there seemed to be a prolonged PR-OS (although not statistically significant) in patients who received DLIs compared with those who did not.…”
Section: Discussioncontrasting
confidence: 57%
“…Limited data suggest the utility of DLI in relapsed lymphoma patients after allo-HCT [6,[15][16][17][18][19][20]. More recently, French investigators showed excellent response rates with DLI in peripheral T cell lymphoma patients who relapsed after allo-HCT [21]. In our study there seemed to be a prolonged PR-OS (although not statistically significant) in patients who received DLIs compared with those who did not.…”
Section: Discussioncontrasting
confidence: 57%
“…Indeed, survival has been shown to plateau after alloSCT [15], even after RIC [16]. There is also a potential effect of donor lymphocyte infusion (DLI) in post-transplant relapse [17], and Kanakry et al reported a reduced incidence of relapse (17% compared to 66%, p = 0.04) in patients who developed GvHD [18]. However, because of high TRM, recommending alloSCT for PTCL remains a matter of debate, and current guidelines limit its use for relapsed or refractory patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 A recent case series including 2 ALKpatients with recurrent ALCL to the skin reported that, when treated with DLI, 1 patient had complete response, and the other had partial response. 12 In addition, another patient with ALCL with relapse to the skin 10 months after chemotherapy and 7 months after allogeneic SCT was treated with DLI and palliative chemotherapy, which led to complete remission more than 3 years later. 13 Of note, both of these reports used DLI after the onset of skin lesions.…”
Section: Discussionmentioning
confidence: 99%